Nomograms for predicting the prognosis of stage IV colorectal cancer after curative resection: A multicenter retrospective study. Issue 4 (April 2015) - Kawai, K.; Ishihara, S.; Yamaguchi, H.; Sunami, E.; Kitayama, J.; Miyata, H.; Sugihara, K.; Watanabe, T.
Abstract Purpose Although stage IV colorectal cancer (CRC) encompasses a wide variety of clinical conditions with diverse prognoses, no statistical model for predicting the postoperative prognosis of stage IV CRC has been established. Thus, we here aimed to construct a predictive model for disease-free survival (DFS) and overall survival (OS) after curative surgery for stage IV CRC using nomograms. Methods The study included 1133 stage IV CRC patients who underwent curative surgical resection in 19 institutions. Patients were divided into derivation (n = 586) and validation (n = 547) groups. Nomograms to predict the 1- and 3-year DFS rates and the 3- and 5-year OS rates were constructed using the derivation set. Calibration plots were constructed, and concordance indices (c-indices) were calculated. The predictive utility of the nomogram was validated in the validation set. Results The postoperative carcinoembryonic antigen (CEA) level, depth of tumor invasion (T factor), lymph node metastasis (N factor), and number of metastatic organs were adopted as variables for the DFS-predicting nomogram, whereas the postoperative CEA level, T factor, N factor, and peritoneal dissemination were adopted for the nomogram to predict OS. The nomograms showed moderate calibration, with c-indices of 0.629 and 0.640 in the derivation set and 0.604 and 0.637 in the validation set for DFS and OS, respectively. Conclusions The nomograms developed were capable of estimating the probability of DFS and OS on the basis of only 4 variables, and may represent useful tools for postoperative surveillance of stage IV CRC patients in routine practice.